Epoxidised natural rubber layered silicates nanocomposites - Madhusoodhanan KN; Varghese Siby (Rubber Science, 2013)
Polymer/layered silicate nanocomposites exhibit remarkable improvement in mechanical and barrier properties compared to their virgin polymers or microcomposites. Nanoclay being organophilic are more compatible with polar polymers. Epoxidised natural rubber (ENR), a polar form of natural rubber is expected to show high affinity and better performance with layered silicates. Epoxidised natural rubber nanocomposites were prepared by melt compounding of ENR having an epoxy content of 50 mole per cent at ambient temperature. Two grades of organically modified montmorillonite (MMT) having layer distances of 2.1 and 1.85 nm were used in this study. Accelerated sulphur curing system was used for the vulcanizationof the composites. For comparison, commercial clay was included in this study and the filler loading was kept at 10 phr in all mixes. The cure characterestics and mechanical properties were evaluated. The dispersion of the silicate in the matrix was studied by transmission electrone microscopy (TEM). The addition of modified MMT to the ENR reduced its cure time and scorch time. The maximumtorque was higher for these composites.The montmorillonite filled composite showed better mechanical properties when compared to the reference material. The enhancement in properties was believed to be due to the partial exfoliation/intercalation of the layered silicates in ENR. Amog the two types of nanoclays, the one having higher inter-higher distance showed better mechanical properties.
Keywords: Epoxidised natural rubber; Epoxidised natural rubber; Exfoliation; Exfoliation; Intercalation; Intercalation; Layered silicate; Layered silicate; Montmorillonite; Montmorillonite; Nanocomposites; Nanocomposites